A population based study of drowning in Canada - Tessa Clemens; Hala Tamim; Michael Rotondi; Alison K. Macpherson (BMC, 2016)
Abstract Background Although water-related fatality rates have changed over time, the epidemiology of drowning in Canada has not recently been examined. In spite of the evidence supporting varying drowning death rates by age, information on how characteristics of drowning incidents differ by age group remains limited. The primary objective of this study was to examine the epidemiology of drowning in Canada. A secondary objective was to describe the characteristics of these drowning incidents as they vary by age group. Methods A retrospective descriptive analysis was conducted using data that were collected for incidents occurring in Canada between January 1, 2008 and December 31, 2012. The main outcome variable was a water-related fatality, in the majority of cases (94 %) the primary cause of death was drowning. Age specific frequencies, proportions and rates per 100,000 population were calculated and compared among six age groups. Results There were 2392 unintentional water-related fatalities identified in Canada between 2008 and 2012. Death rates (per 100,000) varied by age group 0-4 (1.05), 5-14 (0.57), 15-19 (1.27), 20-34 (1.70), 35-64 (1.44), 65+ (1.74). The male to female ratio was 5:1. Differences in the characteristics of drowning by age group were identified across: sex, body of water, urban versus rural location, time of year, activity type, purpose of activity, alcohol involvement, personal flotation device use, accompaniment, and whether a rescue was attempted. Conclusions The study results suggest that there may be a need for drowning prevention strategies that are tailored to specific age groups. Rural areas in Canada may also benefit from targeted drowning prevention.